Transforming Lembu Sejahtera Farmers Group's Product Sales Through Digital Marketing - Israwati Israwati; Hermansyah Hermansyah; Damri SM; Sipnarong Kanchanawongpaisan; Muhammad Raihan; Mailani Azizah (Eastasouth Journal of Effective Community Services, 2025)
Community service at the Lembu Sejahtera Farmers Group in Merempan Village, Siak District, Riau, aims to address the limitations of market reach and conventional marketing for superior cattle breeding. Activities are carried out through problem identification, joint planning, preparation, training and mentoring, and evaluation. A participatory approach involves observation, interviews, focus group discussions (FGDs), and literature review to implement digital marketing strategies. As a result, group members' understanding and skills in digital promotion have improved, local leaders have emerged, new internal institutions have been created, and behavioral transformations have occurred toward independence and technological adaptation. Other impacts include increased sales, income, market expansion, and strengthening the group's position. Sustainability is ensured through partner capacity building, the establishment of an independent Village Breeding Center, and increased group competitiveness in the digital era, supporting sustainable socio-economic transformation and the national meat self-sufficiency program.